فكرة إمام سوفرايوغو عن نشر اللغة العربية في إندونيسيا - Bahruddin Fanani (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2011)
Arabic is the most important means for the generation of Muslims wherever and whenever, since its existence became the main language of the sources of Islamic teachings. In another sense, every Muslim must learn and understand the primary sources of Islam, so they were obliged to learn Arabic. Learning Arabic has long been a focus of attention of the Islamic countries or countries with Muslim majority, to improve his people skills in mastering the Arabic language. The increasing mastery of the Arabic language ability is thought to increase the ability to understand the teachings of Islam. In the end, Islam will be easily implemented into the behavior of Muslim community life. This paper tries to present the points of thought one of the leaders in Indonesia are persistent in developing learning Arabic, especially in college. One figure who was appointed was Dr. Iman Suprayogo, rector of UIN Malang ie, a fairly judged successful in developing the idea of establishment Language Center on campus.